Quercetin potentiates the effect of γδT cells via modulating the expressions of Granzyme B, perforin and IFN-γ and also regulates the Wnt/δ-catenin signalling pathway in human colon cancer cells (Bangladesh Journal of Pharmacology, 2015)
Cancer accounts as one of the leading causes of morbidity and mortality. Recent studies focus on the efficiency of phytochemicals in cancer therapy. Influence of quercetin, a flavonoid on the effect of γδ T cells and Wnt/β-catenin signalling pathway in human colon cancer cells (HT55 and HCT116) was investigated. Quercetin at 15-120 µM was observed to markedly reduce the viability of HT55 and HCT116 cells. Quercetin exposure significantly increased γδ T cell proliferation and also raised the expressions of granzyme B (Gra B), perforin (PFP), and interferon- γ (IFN-γ) in γδ T cells. Reduced β-catenin expression with increased expressions of phosphorylated- β-catenin, axin1 and 2 were observed in HT55 and HCT116 cells on exposure to quercetin. However β-actin expression was found to be not much altered. The results suggest that quercetin was able to efficiently potentiate the effect of γδ T cells and modulate Wnt/β-catenin signalling pathway.